PELAKSANAAN DIVERSI DALAM PENYELESAIAN PERKARA ANAK YANG BERHADAPAN DENGAN HUKUM DI POLRES SIJUNJUNG - Sry Wahyuni; Helfira Citra (JCH (Jurnal Cendekia Hukum), 2018)
This Research discuss diversion implementation by the police station of Sijunjung as the alternatif resolving criminal case children in conflict with law. As for that to be special purpose from this research : the first, describe the diversion implementattion as the alternatif resolving criminal case children in conflict with law; the second, Describe the from of diversion as mediation penal that  implementation in Sijunjung Police station; the third Conclude any obstacles faced in diversion implementation as the alternatif resolving criminal case children in conflict with law of Sijunjung Police station. The result of this research is implementation of diversion can be more optimal. In case to solve the problem of children especially child crime for guarantee legal certanty for children in conflict with law. This process usually settle out of court, that is through diversion based on approach restorative justice in the Sijunjung region. Therefore, not many children are required carry out criminal liability that should in the age of children get contruction according to their age.